Menopause in systemic sclerosis: the impact on clinical presentation in a multicenter cross-sectional analysis from the National Registry of the Italian Society for Rheumatology (SPRING-SIR) - Martina Orlandi; Dilia Giuggioli; Clodoveo Ferri; Rossella De Angelis; Valeria Riccieri; Fabio Cacciapaglia; Silvia Laura Bosello; Veronica Codullo; Gianluigi Bajocchi; Lorenzo Dagna; Corrado Campochiaro; Giacomo De Luca; et al. (Therapeutic Advances in Musculoskeletal Disease, 2025)
Background: Hormonal changes in menopause might interact with the presentation of underlying autoimmune diseases, such as systemic sclerosis (SSc). Objectives: Our study aimed to evaluate the association of (1) current menopausal status, (2) early menopause, and (3) disease onset during fertile or post-menopausal age on SSc clinical phenotype in a large SSc cohort from the Italian Systemic sclerosis Progression INvestiGation (SPRING-SIR) registry. Design: Female SSc patients from the SPRING-SIR registry, fulfilling the American College of Rheumatology (ACR)/European Alliance of Associations for Rheumatology (EULAR) 2013 classification criteria, with data on SSc disease onset, menopausal status, and menopausal age, were eligible. SSc onset was categorized as pre-menopausal if SSc onset happened >1 year before menopause or as post-menopausal onset if it occurred >1 year after menopause. An early menopause was defined by a menopausal age <45 years. Methods: Descriptive statistics and regression models were built to test the association between current menopausal status, pre-menopausal disease onset, and early menopause with SSc-related features. Results: At baseline, 1157/1538 (75%) patients were in menopause, 632 (50.4%) had a pre-menopausal SSc onset, and 130 (14.4%) reported an early menopause. Post-menopausal patients had more frequent limited cutaneous SSc, anti-centromere antibody positivity, interstitial lung disease, and gastrointestinal manifestations. Pre-menopausal onset cases showed more frequent diffuse cutaneous involvement and peripheral vasculopathy. Patients with early menopause had more frequent peripheral vasculopathy and interstitial lung disease, being early menopause an independent risk factor for digital ulcers and lower diffusing capacity of the lung for carbon monoxide. Conclusion: Current post-menopausal status and early menopause may impact SSc presentation, being associated with vascular and gastrointestinal manifestations. Menopausal status and age should therefore be thoroughly addressed, aiming at better disease management.